Personal integrity and social responsibility in decision making process: the case of western Australian small business owners - Sarif, Suhaimi Mhd (2010)
Personal integrity and social responsibility are very important values to make ethical and profitable organizational decisions. Personal integrity requires the decision makers to optimize their personal discretion in making trusted, credible, and profitable business decisions. Likewise, the social responsibility component sought decision makers to make decisions that providing benefits and repelling harms to the stakeholders. Both values are pertinent in the modern contexts that full with frauds, corruptions, and crime of breach of trusts (CBT).This paper investigates the perceptions of Western Australian small business owners toward the challenge to incorporate personal integrity and social responsibility in their decision making process. The study used personal interview technique with open ended interview questions to obtain the views of 15 business owners from Perth, Western Australia. More than half of the interviewees contended that three factors, namely the personal ethics, professional training, and religious belief, motivated decision makers to incorporate personal integrity and social responsibility in their decisions. The remaining interviewees argued that the need to meet the economic and legal requirements is the main factor for incorporating the two elements into their decisions. Nevertheless, the results of the study were not conclusive and cannot be generalized considering limitations on small number of interviewees and the location of the business owners. The study proposed that future research to use personal interview and self administered survey with more small business owners from other major cities in Australia.